Implementasi Media Pembelajaran Berbasis Aplikasi Canva Dalam Meningkatkan Kreativitas Belajar Siswa Pada Mata Pelajaran PAI - Khoir, Anton Iftakhul; Surur, Shobihus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research seeks to investigate the application of Canva-based learning media in enhancing students' creativity in the subject of Islamic Religious Education (PAI). The study is motivated by the issue of low student creativity, which stems from the conventional, teacher-centered teaching methods commonly used in PAI classes, with limited active interaction. Canva, as a practical and easily accessible digital graphic design platform, is adopted as an innovative learning tool to Encourage active involvement of students and foster creative expression. The research employs an approach of qualitative descriptive nature. Data were collected through direct observing and conducting interviews with various informants, including the School Principal, PAI teachers, and students of SMPN 1 Jombang. Data obtained were analyzed using source triangulation techniques to ensure the validity of the information. The study's findings reveal that: (1) Canva-based learning media are implemented in various forms of visual works such as presentations, posters, and infographics, created by both teachers and students; (2) the use of Canva motivates students to engage more actively in the learning process process, better able to express their ideas through visual media, and more confident during group presentations; and (3) several supporting factors were identified, including the availability of digital devices and high student enthusiasm. However, some obstacles remain, such as internet connectivity issues and limited projector (LCD) facilities in certain classrooms.